The relationship of providing lemon aroma therapy with mother's anxiety in care of newborn babies in the health center area - Tiarnida Nababan; Buulolo, Arilia; Lubis, Arnisa; Kholid, Arisa Rahmah; Barros, Arlida; Arnisfu, Arnisfu (Jurnal EduHealth, 2024)
Worry or anxiety is tension, feeling no safety, and the concerns that arise because something will happen that isn't fun, but the source part is known. Worry is an emotion without a specific object because it is No known and preceded by experience. Worry differs from fear. Study This aim is to determine the effectiveness of providing lemon aromatherapy for lower-level anxiety in postpartum mothers at the Community Health Center, and also the influence of lemon therapy. Benefits of research: This gives information and adds knowledge to carry out care. Midwifery is complementary, specifically in overcoming maternal anxiety postpartum. Deep-method study This is a quasi-experiment with a design pre-test and post-test with a control design. Samples used in the study This is namely postpartum mothers who experience worry as many as 28 people. Research result This shows that giving lemon aromatherapy is effective in lowering maternal anxiety postpartum in the work area public health center, expressed with a P value of <0.05. Advice from the study This is expected of health workers to provide counseling to the public, especially mothers, related to giving aroma therapy as a non-pharmacological treatment given to mothers who experience anxiety. Postpartum period, or postpartum period, is term for 6 weeks, first after birth. During this, mother and family will experience lots of changes, including changes in structure and function in the family. In stages, this mother starts to adapt to the new role. Therefore, there is seldom impact change psychological mother among them that is worried. Therefore, that required some intervention to reduce impact anxiety, and one of them was the lemon aromatherapy method. Study this aim to know the influence of lemon aromatherapy (Citrus limon) against level of worry in mothers postpartum.